A Pseudoscorpion's Promising Pinch: The venom of Chelifer cancroides contains a rich source of novel compounds. (15th October 2021) - Krämer, Jonas; Peigneur, Steve; Tytgat, Jan; Jenner, Ronald A.; van Toor, Ronald; Predel, Reinhard
Abstract: With pedipalps modified for venom injection, some pseudoscorpions possess a unique venom delivery system, which evolved independently from those of other arachnids like scorpions and spiders. Up to now, only a few studies have been focused on pseudoscorpion venom, which either identified a small fraction of venom compounds, or were based on solely transcriptomic approaches. Only one study addressed the bioactivity of pseudoscorpion venom. Here, we expand existing knowledge about pseudoscorpion venom by providing a comprehensive proteomic and transcriptomic analysis of the venom of Chelifer cancroides . We identified the first putative genuine toxins in the venom of C . cancroides and we showed that a large fraction of the venom comprises novel compounds. In addition, we tested the activity of the venom at specific ion channels for the first time. These tests demonstrate that the venom of C . cancroides causes inhibition of a voltage-gated insect potassium channel (Shaker IR) and modulates the inactivation process of voltage-gated sodium channels from Varroa destructor . For one of the smallest venomous animals ever studied, today's toolkits enabled a comprehensive venom analysis. This is demonstrated by allocating our identified venom compounds to more than half of the prominent ion signals in MALDI-TOF mass spectra of venom samples. The present study is a starting point for understanding the complex composition and activity of pseudoscorpion venom and provides a potential rich source of bioactive compounds useable for basic research and industrial application. Highlights: First comprehensive proteo-transcriptomic analysis of pseudoscorpion venom. The venom contains a large number of novel peptide compounds. Electrophysiological activity tests with pseudoscorpion crude venom.